Urgensi Lex Specialis Dalam Pelaksanaan Over The Top (OTT) Video Streaming Di Indonesia [Urgency of Lex Specialis in the Implementation of Over The Top (OTT) Video Streaming in Indonesia] - Confido, Jemy Vestius; Komala, Angelita Patricia (Jurnal Hukum Visio Justisia, 2023)
In the last few decades, technology has evolved rapidly and this has led to the changes of people’s behavior, including the way of enjoying videos. Video streaming Over The Top (OTT) as part of the digital services, which is currently becoming popular, is video streaming services that enable viewers to enjoy movies or TV shows through the Internet such as Netflix, Disney+HotStar, Amazon Prime Video, Hulu, Mola, HBO GO/NOW, YouTube and Vidio. The traditional/conventional TV methods like cable or satellite TV shall follow the Law Number 32 of 2002 concerning Broadcasting (Broadcasting Law). According to Article 1 Paragraph (2) of the Broadcasting Law, broadcasting shall be defined as the activity of broadcasts and/or transmission on land, at sea, or in space by using a radio frequency spectrum by air, cable, and/or other media to be received simultaneously and concurrently by the public using broadcast receiving equipment. However, OTT Services which are Internet-based broadcasting is not considered as part of the "broadcast" category in the Broadcasting Law and consequently the application of lex specialis principle should be considered. The objective of this research is to analyze the regulations pertaining to video streaming services which are part of OTT services in Indonesia and to identify legal vacuum according to the principles of legal certainty and justice. This research study uses normative legal research methodology by conducting examination on the positive law (ius positum). The conclusions of this research identify that Article 1 Paragraph (2) of the Broadcasting Law does not include the OTT Services which are Internet-based broadcasting and subsequently there is no comprehensive regulation in Indonesia to govern OTT services to obtain legal certainty and therefore the arrangement and its implementation must be prepared. Bahasa Indonesia Abstrak: Dalam beberapa dekade terakhir, teknologi telah berkembang secara cepat dan hal ini telah membawa perubahan pada perilaku masyarakat termasuk dalam menikmati layanan video. Layanan Over The Top (OTT) video streaming sebagai bagian dari layanan digital yang saat ini populer merupakan layanan video streaming yang menyediakan akses kepada film atau acara TV melalui Internet seperti Netflix, Disney+HotStar, Amazon Prime Video, Hulu, Mola, HBO GO/NOW, YouTube dan Vidio. Metode TV tradisional/konvensional seperti kabel atau satelit TV tunduk kepada Undang-Undang Nomor 32 Tahun 2002 tentang Penyiaran (UU Penyiaran). Menurut Pasal 1 ayat (2) UU Penyiaran, penyiaran diartikan sebagai aktivitas memancarkan dan/atau mentransmisikan di darat, laut, atau udara dengan menggunakan spektrum frekuensi radio di udara, kabel dan/atau media lainnya untuk diterima secara serentak dan bersamaan oleh masyarakat dengan menggunakan perangkat penerima. Namun demikian, layanan OTT yang berbasis Internet tidak dapat dikelompokkan sebagai bagian dari penyiaran dalam UU Penyiaran sehingga perlu dipertimbangkan penerapan asas lex specialis. Tujuan dari penelitian ini adalah untuk menganalisis regulasi terkait layanan video streaming yang merupakan bagian dari layanan OTT di Indonesia serta untuk menemukan kekosongan hukum sesuai dengan prinsip-prinsip kepastian hukum. Penelitian ini menggunakan metode normative legal research dengan melakukan pengkajian pada hukum positif (ius positum). Kesimpulan dari penelitian ini mengindikasikan bahwa Pasal 1 ayat (2) UU Penyiaran tidak mencakup layanan OTT yang berbasis Internet sehingga bisa disimpulkan bahwa belum ada regulasi yang komprehensif di Indonesia untuk mengatur layanan OTT demi terciptanya kepastian hukum sehingga peraturan dan implementasinya perlu disiapkan.